2011
DOI: 10.1101/gad.2000211
|View full text |Cite
|
Sign up to set email alerts
|

A kinase shRNA screen links LATS2 and the pRB tumor suppressor

Abstract: pRB-mediated inhibition of cell proliferation is a complex process that depends on the action of many proteins. However, little is known about the specific pathways that cooperate with the Retinoblastoma protein (pRB) and the variables that influence pRB's ability to arrest tumor cells. Here we describe two shRNA screens that identify kinases that are important for pRB to suppress cell proliferation and pRB-mediated induction of senescence markers. The results reveal an unexpected effect of LATS2, a component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 89 publications
6
95
0
Order By: Relevance
“…Recent studies have shown links between the Hippo pathway and the pRB (retinoblastoma) pathway in the context of cellular senescence. [44][45][46][47] The latter studies show a role for Lats2 in mediating repression of E2F target genes by pRB in senescence. These studies induced senescence through oncogene expression or serum withdrawal.…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies have shown links between the Hippo pathway and the pRB (retinoblastoma) pathway in the context of cellular senescence. [44][45][46][47] The latter studies show a role for Lats2 in mediating repression of E2F target genes by pRB in senescence. These studies induced senescence through oncogene expression or serum withdrawal.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, it is considered as an important tumor suppressive mechanism. 2,3 However, senescent cells are still metabolically active and ultimately develop senescence-associated secretory phenotypes, which participate in tumor suppression, tumor promotion, aging, and tissue repair. 4 SASPs composed of soluble proteins (cytokines, chemokines, and growth factors), secreted proteases and secreted insoluble proteins/extracellular matrix components may influence the fate of unirradiated neighboring cells, which is known as the bystander effect.…”
Section: Introductionmentioning
confidence: 99%
“…The recently published results of shRNA screens give a glimpse of the types of signaling pathways that impact pRB function. 4 By quantifying the changes in cell number and the expression of senescence-associated β-galactosidase, we identified 39 kinases that were required for efficient pRB-inhibition of cell proliferation and 41 kinases that were necessary for pRB to establish a senescence-like state in SaOS2 cells, an osteosarcoma cell line that is mutant for RB1. These results demonstrate that there are many ways to enhance or suppress the ability of pRB to impose a permanent cell cycle arrest.…”
mentioning
confidence: 99%
“…the kinases listed promote prB-dependent G 1 arrest or senescence. 4 shown in red are the subset of kinases that were also found in shrNa-based screens to support cell viability in cells that express mutant K-ras. [5][6][7] asterisks indicate that related (but non-identical) kinases were identified in the different types of screens.…”
mentioning
confidence: 99%
See 1 more Smart Citation